Blood-based quantification of Aβ oligomers indicates impaired clearance from brain in ApoE ε4 positive subjects - Lara Blömeke; Fabian Rehn; Marlene Pils; Victoria Kraemer-Schulien; Anneliese Cousin; Janine Kutzsche; Tuyen Bujnicki; Silka D. Freiesleben; Luisa-Sophie Schneider; Lukas Preis; Josef Priller; Eike J. Spruth; et al. (Communications Medicine)
Abstract Background Quantification of Amyloid beta (Aβ) oligomers in plasma enables early diagnosis of Alzheimer’s Disease (AD) and improves our understanding of underlying pathologies. However, quantification necessitates an extremely sensitive and selective technology because of very low Aβ oligomer concentrations and possible interference from matrix components. Methods In this report, we developed and validated a surface-based fluorescence distribution analysis (sFIDA) assay for quantification of Aβ oligomers in plasma. Results The blood-based sFIDA assay delivers a sensitivity of 1.8 fM, an inter- and intra-assay variation below 20% for oligomer calibration standards and no interference with matrix components. Quantification of Aβ oligomers in 359 plasma samples from the DELCODE cohort reveals lower oligomer concentrations in subjective cognitive decline and AD patients than healthy Control participants. Conclusions Correlation analysis between CSF and plasma oligomer concentrations indicates an impaired clearance of Aβ oligomers that is dependent on the ApoE ε4 status.